KEY ISSUES IN E-BANKING STRENGTHS AND WEAKNESSES: THE CASE OF TWO JORDANIAN BANKS - Rifat O. Shannak (European Scientific Journal, ESJ, 2013)
﻿This explanatory research paper uses mixed methods. Research about e-banking has been conducted from different angles on different topics by a number of researchers. The paper aims to examine the current status of Jordan’s e-banking industry, identify its strengths and weaknesses, and use the findings in formulating future recommendations to make a contribution to knowledge in the chosen area.The choice of the topic was informed by previous studies and experiences of the researcher and his former students from different countries but currently focuses on the e-banking industry in Jordan.The methodology used to achieve the research objectives included carrying out interviews with two local banking executives, a direct questionnaire for banking customers, and the review of the extant literature. The research commenced by formulating four hypotheses that address the positive impact of e-banking for both the banks and their clients. However, a limited size sample was selected due to research limitations. The orientation of the paper turned out to be explanatory and in the direction of being a case study within the Jordanian context. This exploratory research therefore, focused on three main dimensions of e-banking in Jordan namely; Infrastructure readiness, behavioral influences, and the regulatory coverage.The findings indicated that while the infrastructure is advanced in comparison to some of the other regional examples, it was still below the Western standards. It also has been established that the Jordanian e-banking is still not trusted enough by the individual clients. Finally, the legal or regulatory coverage in Jordan was found to be not fully satisfactory yet, although not very different from what exists in some of the most advanced country examples that it was benchmarked with. Some important recommendations to enhance the e-banking industry are presented, such as; focusing more on the mobile-functionalities and services for being more advanced than internet services in Jordan, enhancing the broader e-commerce regulations that are weakening the more advanced local e-banking regulations, and launching local awareness and familiarization campaigns which could be undertaken by Jordanian banks.